The Effect of Enterprise Risk Management, Firm Size, Profitability, and Leverage on Firm Value - Armanto Witjaksono; Ratna Puspita Sari (EAJ (Economic and Accounting Journal), 2021)
The purpose of this study is to investigate the effect of enterprise risk management, firm size, profitability, and leverage on the worth of property and assets companies listed on the Indonesia securities market during 2015-2017. the tactic of knowledge analysis during this study is multiple regression toward the mean analysis using SPSS software version 25. The results of the study indicate that the scale of the corporate doesn't have an influence on the worth of the corporate. Other variables like profitability and leverage have a big positive effect on firm value, while the applying of enterprise risk management to property and assets companies listed on the Indonesia securities market incorporates a significant negative effect on firm value. it had been concluded that enterprise risk management, profitability and leverage affect the worth of the corporate